How elevated pCO2 modifies total and metabolically active bacterial communities in the rhizosphere of two perennial grasses grown under field conditions - Jossi, Maryline; Fromin, Nathalie; Tarnawski, Sonia; Kohler, Florian; Gillet, François; Aragno, Michel; Hamelin, Jérôme (My University, 2006)
The response of total (DNA-based analysis) and active (RNA-based analysis) bacterial communities to a pCO2 increase under field conditions was assessed using two perennial grasses: the nitrophilic Lolium perenne and the oligonitrophilic Molinia coerulea. PCR- and reverse transcriptase-PCR denaturing gradient gel electrophoresis analysis of 16S rRNA genes generated contrasting profiles. The pCO2 increase influenced mainly the active and root-associated component of the bacterial community. Bacterial groups responsive to the pCO2 increase were identified by sequencing of corresponding denaturing gradient gel electrophoresis bands. About 50% of retrieved sequences were affiliated to Proteobacteria. Our data suggest that Actinobacteria in soil and Myxococcales (Deltaproteobacteria) in root are stimulated under elevated pCO2.
Keywords: Bacterial community; 16S rRNA; DGGE; global change; carbondioxide; FACE